Do instrumental and symbolic factors interact in influencing employer attractiveness and job pursuit intention?. Issue 4 (18th September 2018) - Kumari, Shweta; Saini, Gordhan K.
Abstract : Purpose: The changing demographics of talent market calls for a better understanding of the expectations of diverse job seekers. However, there is limited research on employer attractiveness (EA) factors which cover the expectations of new generation job seekers. The purpose of this paper is to examine the effect of career growth opportunities (CGO), work–life benefits (WLB) and corporate social responsibility (CSR) reputation on the perceived attractiveness of an organization as an employer and the job pursuit intention (JPI) of job seekers. Design/methodology/approach: A 2 (CGO: many vs limited)×2 (WLB: many vs limited)×2 (CSR reputation: high vs low) between-subjects experimental design was used for this study. A total of 240 respondents participated in the study. Findings: The results showed that provision of CGO had the highest effect on both EA and JPI. This effect was strong enough to compensate for limited WLB and a low CSR reputation. A significant interaction effect between CGO and CSR reputation revealed that the effect of CSR reputation on EA depends on the availability of many or limited CGO. Originality/value: The study contributes and expands literature on attributes relevant in job choice decisions by providing useful insights regarding how job seekers weigh these attributes while making an employment choice. Also, the study offers suggestions for designing organizations' recruitment strategy for attracting talent.